THE MECHANICAL PROPERTIES OF POLYMER-MORTAR COMPOSITES - M. Fahad, Besma; M. Eweed, Khalid; M. Abdalateef, Yaser (Journal of Engineering and Sustainable Development, 2015)
The polymer-mortar composites have several benefits, including corrosion resistance, high strength and modulus values compared to their low density, acceptable deformability, tailored design and excellent formability. This enables the fabrication of new elements and the structural rehabilitation of the existing parts made of traditional materials. In this work two sets of mixtures were prepared that consist of mortar and polymer to fabricate the polymer-mortar composite. The first set include mortar with ratio (1:1) (cement-sand) without water, while the other set include mortar with ratio (1:2) (cement-sand) without water. The polymer was epoxy which is added to the mortar after mixing the resin with the hardener in proportion of (1:3). Each set consists of different percentage of polymer (50:50, 40:60 and 30:70). to obtain Several results were obtained such as density, were the highest value was about 1906.4 kg/m3 for (1:1).